Physiological integration enhanced the tolerance of Cynodon dactylon to flooding. (30th December 2014) - Li, Z. J.; Fan, D. Y.; Chen, F. Q.; Yuan, Q. Y.; Chow, W. S.; Xie, Z. Q.; Elzenga, T.
Abstract Many flooding‐tolerant species are clonal plants; however, the effects of physiological integration on plant responses to flooding have received limited attention. We hypothesise that flooding can trigger changes in metabolism of carbohydrates and ROS (reactive oxygen species) in clonal plants, and that physiological integration can ameliorate the adverse effects of stress, subsequently restoring the growth of flooded ramets. In the present study, we conducted a factorial experiment combining flooding to apical ramets and stolon severing (preventing physiological integration) between apical and basal ramets of Cynodon dactylon, which is a stoloniferous perennial grass with considerable flooding tolerance. Flooding‐induced responses including decreased root biomass, accumulation of soluble sugar and starch, as well as increased activity of superoxide dismutase (SOD) and ascorbate peroxidase (APX) in apical ramets. Physiological integration relieved growth inhibition, carbohydrate accumulation and induction of antioxidant enzyme activity in stressed ramets, as expected, without any observable cost in unstressed ramets. We speculate that relief of flooding stress in clonal plants may rely on oxidising power and electron acceptors transferred between ramets through physiological integration.